Penerapan Kurikulum Merdeka pada Pembelajaran Bahasa Indonesia di Sekolah Dasar - Arrasyid, Muhamad Miftahurrozaq; Ernawati, Asih (Asian Journal of Early Childhood and Elementary Education, 2024)
This qualitative research aims to describe (1) how Kurikulum Merdeka is implemented and (2) what difficulties are faced whilst implementing the curriculum in Indonesian language learning. The subjects of this research were the principal, fifth grade teacher and students. Data were collected through interviews, observation and documentation. The data then analyzed utilizing Miles and Huberman model. The study showed that the implementation of Merdeka Kurikulum of Bahasa Indonesia in fifth grade classroom is quite effective. It is said to be quite effective because the teaching and learning process runs quite well and is in accordance with the learning objectives. However, a few problems existed which were handled by the school administrator.